The Effect of Mathematics Subject on Accounting Students of Private and State Universities in Iran - Mahdi MORADI; Mahdi SALEHI; Somayeh KHALILIANMOVAHED (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
It is proved that mathematics ability effect on understanding in principles of accounting in some research but number of these investigations is very low. The main purpose of this research is to explore the relationship between influence of mathematics ability on understanding in principles of accounting through investigating relationship between students score in principle of accounting lesson and students score on mathematics pre-test and math score. Statistical sample consists of 184 own state university’s students and 105 private university’s students that they had selected principle of accounting lesson, involved 120 accounting fields students, 84 management students and 85 economic students. Pre-test only involve areas of mathematics that have more impact on understanding in principles of accounting. Results showed students arithmetical skills are high in both universities and conceptual skills in own state university and algebra skills in private university are low and mathematics skills has a significant effect on principles of accounting score. In addition, students’ self-confidence beliefs and its impact on students score in mathematics and principles of accounting lessons were explored. Results showed students who had high level of self-confidence had gotten better scores